Analysis of the Contribution of the Creative Economy to Job Growth in Medan City - Muharani Fiannisa; Lasman Eddy Bachtiar (Journal of Management and Business Analytics, 2025)
This study analyzes the contribution of the creative economy to employment growth in Medan City. The results of the study show that the creative economy sector, especially culinary, handicrafts, publishing, and fashion, has a significant role in creating job opportunities. These sectors are able to absorb a large number of workers, both on the scale of micro, small, and medium enterprises. However, the development of the creative economy still faces various challenges, such as limited access to capital, lack of supporting infrastructure, and suboptimal regulations. To overcome these obstacles, a collaborative strategy is needed between the government, the private sector, and the creative community to create an environment conducive to the growth of the creative economy. Through the right policies, financial support, and innovation, the creative economy can be the main motor in increasing employment and community welfare in the city of Medan.